Conversion Of Local Government Financial Report (LKPD) Cash Toward Accrual Basis To Become Acrual Basis (Case Study in Local Government of Cirebon City) - rusmana, oman (Prosiding Seminas Competitive Advantage, 2011)
ABSTRAK Tujuan penelitian untuk mengetahui pengakuan, pengukuran, pengungkapan di dalam basis Cash Toward Accrual (CTA) sesuaidengan PP 24 Tahun 2005 dan dalam basis Accrual sesuai dengan PP 71 Tahun 2010. Penelitian ini berusaha mengetahui perbedaan mendasar dalam hal pengakuan, pengukuran, pengungkapan antara basis CTA dan basis Accrual. Selain itu, untuk mengetahu konversi LKPD di Pemerintah Kota Cirebon (Pemkot) sesuai SAP.Penelitian ini dilakukan pada LKPD periode 2008 dan 2009 yang telah diaudit. Penelitian ini menggunakan uji artikulasi, persamaan akuntansi, dan konversi LKPD sesuai basis akrual. Hasil penelitian menunjukkan perbedaan dalam hal pengakuan, pengukuran, dan pengungkapan pada SAP basis CTA dan SAP basis akrual. LKPD berbasis CTA setelah dikonversi sesuai SAP basis accrual belum sesuai, karena jumlah nominal Ekuitas Akhir pada LPE tidak sama dengan jumlah nominal Ekuitas Akhir pada Neraca, sehingga penyusunan LO, LPE, dan Neraca pada Pemkot Cirebon belum mempunyai artikulasi yang tepat. Kata kunci: kas menuju akrual, akrual, artikulasi, persamaan akuntansi, konversi ABSTRACT This research aimed to know recognition, measurement, and disclosure in the regime of Cash Toward Accrual (CTA) basis according to Government Regulation (GR) 24 Year 2005 and accrual basis according to GR 71 Year 2010. This research endeavours to know the ultimate  differences between CTA and Accrual basis. In addition, this research to determine the conversion LKPD in Cirebon City Government in accordance with SAP. The research was conducted in audited LKPD year 2008 and 2009. This study uses tests of articulation, accounting equation, and the conversion LKPD appropriate accrual basis. The results showed differences in terms of recognition, measurement, and disclosure in the SAP database and SAP CTA accrual basis. LKPD after conversion according to CTA-based SAP has not been appropriate accrual basis, because the nominal amount of equity at the end of LPE is not equal to a nominal amount on ending the Balance Sheet Equity End, so the preparation of LO, LPE, and Balance Sheet in Cirebon municipal government does not have the proper articulation. Keywords: cash toward accrual, accrual, articulation, accounting equation, conversion